2018
DOI: 10.2214/ajr.17.18186
|View full text |Cite
|
Sign up to set email alerts
|

Incidental Pulmonary Embolism After Coronary Artery Bypass Surgery: Long-Term Clinical Follow-Up

Abstract: Incidental PE after coronary artery bypass grafting is found in approximately 6% of patients undergoing postoperative coronary CT angiography, and most PEs resolve spontaneously without anticoagulation. No patient in this study died or had recurrent PE during a median follow-up period of 53 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Previous studies showed similar 10–12 or lower mortality 13,14 in the iPE cancer patients. Also, in patients with iPE diagnosed after coronary bypass survival was very good despite the lack of anticoagulation in the majority of patients 16 . The reason for this discrepancy is not apparent but could be related to de relatively small number of patients 10–13,16 or by excluding patients with iPE if they had retrospectively established symptoms that may be related to PE 13,14 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies showed similar 10–12 or lower mortality 13,14 in the iPE cancer patients. Also, in patients with iPE diagnosed after coronary bypass survival was very good despite the lack of anticoagulation in the majority of patients 16 . The reason for this discrepancy is not apparent but could be related to de relatively small number of patients 10–13,16 or by excluding patients with iPE if they had retrospectively established symptoms that may be related to PE 13,14 .…”
Section: Discussionmentioning
confidence: 99%
“…In the group of patients with trauma, 24% had iPE 15 . Among patients with coronary artery bypass grafting incidence of postoperative PE noted on routine follow‐up imaging was 6.2% 16 . Even in a nonhigh‐risk group of 7019 patients with coronary artery disease, the incidence of iPE was 1.1% 7 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, these patients should be instructed to quit smoking as early as possible to reduce postoperative APE. Previous studies [37][38][39] have shown that occurrence of APE is positively correlated with the operation time. Our study showed that the possibility of APE occurring increased as the operation time increased, which is consistent with related study results.…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed that the possibility of APE occurring increased as the operation time increased, which is consistent with related study results. [37][38][39] A prolonged operation time increases stimulation to the body, and activates and aggregates neutrophils on the surface of the lungs through a series of inflammatory reactions. This then causes damage to endothelial factors of the lungs, leading to formation of thrombi.…”
Section: Discussionmentioning
confidence: 99%